2013
DOI: 10.2174/1385272811317100011
|View full text |Cite
|
Sign up to set email alerts
|

Selective Monoetherification of 1,4-Hydroquinone Promoted by NaNO2

Abstract: Catalytic amounts of NaNO2 are able to successfully promote the reaction between 1,4-hydroquinone and methanol under acidic conditions, affording selectively the corresponding mequinol in excellent isolated yields. According to the proposed reaction mechanism, the semi-quinone intermediate, generated in situ from the corresponding hydroquinone by NO2 oxidation, is the real reactive species, undergoing nucleophilic attack onto the alcoholic molecule. Experimental evidences emphasize the key role of NO2. After o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…1) whose ubiquitous presence in many aspects of organic matter has motivated an extensive number of experimental and theoretical studies. [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] Quinhydrone is made by two units, namely p-benzoquinone and hydroquinone and it is known from a century and an half, being rst discovered in 1844 by Wöhler. 41 It can be prepared by a 1 : 1 mixture of the two components or just by partial reduction of p-benzoquinone in ethyl alcohol.…”
Section: Introductionmentioning
confidence: 99%
“…1) whose ubiquitous presence in many aspects of organic matter has motivated an extensive number of experimental and theoretical studies. [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] Quinhydrone is made by two units, namely p-benzoquinone and hydroquinone and it is known from a century and an half, being rst discovered in 1844 by Wöhler. 41 It can be prepared by a 1 : 1 mixture of the two components or just by partial reduction of p-benzoquinone in ethyl alcohol.…”
Section: Introductionmentioning
confidence: 99%
“…Correale et al [ 6 ] developed a process for monoetherification of HQ by in‐situ generation of BQ via oxidation of HQ in the presence of hydrogen peroxide. A similar mechanism was applied by Gambarotti et al [ 8 ] for selective monoetherification of HQ using sodium nitrite as the oxidizing agent and found a higher yield of 4MP (>99%). Lee et al [ 9 ] and Park et al [ 4 ] reported alkali metal ion‐exchanged zeolite catalysts for liquid phase alkylation of HQ and methanol in a high‐pressure batch reactor with 84% selectivity and 95% conversion at 513 K temperature, 960 min reaction time, and approximately 4.55 × 10 6 Pa pressure over Cs‐NaX zeolite.…”
Section: Introductionmentioning
confidence: 74%
“…Several methods have been reported for the mono-derivatization of symmetrical diols, such as selective mono-tosylation, 18 mono-tetrahydropranylation, 19 mono-dithiocarbonylation, 20 and mono-acylation. 21 Very few reports 22 , 23 for the mono-etherification of diols to tert -butylether are reported with a limited substrate scope. We have successfully demonstrated the decarboxylative etherification protocol using Yb(OTf) 3 as a catalyst for the mono-protection of octan-1,8-diol ( Table 4 , entry 1), wherein a moderate yield of the desired product ( 13 ) was obtained particularly after lowering the concentration of the reaction (0.5 M).…”
Section: Resultsmentioning
confidence: 99%
“…CDCl 3 ): δ 1.54 (s, 9H, C2′H, CH 3 ),6.77 (t, J = 7.5 Hz, 1H, ArH),6.87 (d, J = 8.3 Hz, 1H, ArH), 7.31−7.37 (m, 1H, ArH), 7.70 (dd, J = 7.9, 1.5 Hz, 1H, ArH), 10.96 (s, 1H, OH) 13. C NMR (125 MHz, CDCl 3 ): δ 28.2 (C2′, −C(CH 3 ) 3 ), 82.7 (C1′, −C(CH 3 ) 3 ), 113.9 (C1, ArC−), NMR (100 MHz, CDCl 3 ): δ 14.1 (C12, CH 3 ),22.7 (C3, CH 2 ), 25.1 (C10, CH 2 ), 28.1 (C2′, −C(CH 3 ) 3 ), 29.1, 29.3, 29.3, 29.5, 29.6, 31.9 (C4, C5, C6, C7, C8, C10, C11, CH 2 ), 35.6 (C2, CH 2 ), 79.8 (C1′, −C(CH 3 ) 3 ), 173.3 (CO). 5.1.1.16. tert-Butyl Oleate (17).…”
mentioning
confidence: 88%